Male-female wage differentials in Ireland - Callan, Tim (Economic & Social Studies, 1991)
The persistence of sizeable male-female earnings differentials despite the introduction of a range of anti-discrimination measures has been a focus of concern in many countries. In Ireland the ratio of female to male wage rates rose by about 8 percentage points between 1975 and 1980, following the implementation of equal pay legislation (1975) and anti-discrimination legislation (1977); but since that time the ratio has been approximately stable at about 68 per cent. The current situation is, therefore, not untypical of that in many other countries.
Keywords: Gender wage differentials; Ireland; Equality; Wage differentials